Predicting particle critical supersaturation from hygroscopic growth measurements in the humified tandem differential mobility analyzer - Brechtel, Fredrick J., author (Colorado State University. Libraries, 1998)
A new method is described to estimate the critical supersaturation of a quas1- monodisperse, dry particle population composed of pure salts using measurements of hygroscopic growth at several relative humidities below 100%. We describe how Kohler theory may be used to derive two chemical composition dependent parameters, with appropriate accounting for solution effects through a simplified model of the osmotic coefficient. Using a regression routine, the two unknown chemical parameters are derived by fitting the Kohler model to the results from hygroscopic growth experiments. The derived parameters are then used in the Kohler model to calculate critical supersaturations for given dry particle size. From these studies, it is possible to derive the cloud condensation nucleus spectrum if simultaneous measurements of the total number size distribution are made and a sufficient number of critical supersaturations for different particle sizes are determined to characterize the cloud condensation nucleus sub-population of the total particle population. This work represents one of the first, detailed studies on the relationships between particle hygroscopicity and CCN activity using simultaneous measurements of droplet growth and particle critical supersaturation on particles composed of pure salts. In this work we present the theory and methodology that allow the critical supersaturation to be derived from hygroscopic growth measurements, and perform numerical sensitivity studies with respect to assumptions made and anticipated uncertainties in key input parameters to the Kohler model. Laboratory studies are conducted on particles composed of NaCl, (NH4 )2SO 4 , NH4 HSO4 , internally and externally mixed N aC1-(NH4 ) 2SO4 to validate the technique. Studies on ambient particles are also conducted to test if the technique can predict accurate values of Scrit for particles of unknown chemical composition. Results from numerical studies show that for particle diameters of 40 and 100 nm, the maximum errors in critical supersaturations derived using the proposed method are between ±15%. This error is similar to the observed average experimental uncertainty in estimates of the critical supersaturation of -0.6%±11 % determined from CCN studies on particles of known composition. Laboratory studies demonstrate that the critical supersaturation can be derived from hygroscopic growth measurements within experimental uncertainties for the particles of known chemical composition examined in this work. The largest observed differences (-3% to -62%) between HTDMA and CCN derived values of Scrit occurred for ambient particle samples where the chemical composition was unknown and most likely contained a significant amount of hydrophobic material. The numerical and laboratory studies indicate that the proposed technique can establish quantitative relationships between particle size and hygroscopic growth and cloud condensation nucleus activity. The method should help reduce uncertainties in estimates of the indirect effect of particles on climate by allowing more commonly measured aerosol properties, for example particle size and hygroscopic growth, to be directly related to the particle critical supersaturation.
September 25, 1998.
Keywords: Aerosols -- Measurement; Cloud physics; Atmospheric chemistry